Academics must keep abreast of teaching methods - William K., Lim (New Straits Times Press, 2023)
The upcoming review of the National Higher Education Policy by the Higher Education Ministry is timely to steer the national conversation towards improving teaching. The ministry's 2018 guidelines titled "Framing Malaysian Higher Education 4.0: Future-Proof Talents" included Future Ready Curriculum, with its 21st-century Learning and Teaching delivery that advocates learning without lectures. The staff appraisal ecosystem must no longer reward the giving of lectures. The Higher Education Leadership Academy (Akept) should train pedagogy experts in each university to act as consultants during curriculum development and review.